The Effect of Health Education on Improving Knowledge About Anemia Among Adolescent Girls in MTsN VI Pidie - Khaira Maulina; Yusni Yusni; Said Usman; Irwan Saputra; Nasrul Zaman (International Journal of Public Health, 2025)
Anemia remains one of the leading public health issues among adolescent girls in Indonesia, including in Pidie District. Insufficient iron intake and low awareness and knowledge of anemia are major contributors to its high prevalence. Health education is recognized as an effective strategy to improve adolescents’ understanding of anemia.Objective: This study aimed to assess the effect of health education on increasing knowledge about anemia among adolescent girls at MTsN VI Pidie, Pidie District.Methods: A quantitative approach with a quasi-experimental design (one-group pretest-posttest) was employed. A total of 30 first-grade female students from MTsN VI Pidie were selected through purposive sampling. The intervention involved the delivery of health education on anemia via an educational video. Knowledge levels were measured before and after the intervention using pretest and posttest questionnaires. Data were analyzed using the Wilcoxon signed-rank test and paired t-test.Results: The analysis showed a statistically significant improvement in the participants’ knowledge following the intervention. The average posttest scores were notably higher than the pretest scores, indicating a positive effect of the health education intervention (p < 0.05).Conclusion: Digital media-based health education is effective in enhancing knowledge about anemia among adolescent girls. This approach is recommended for broader implementation in adolescent health promotion programs, particularly in the prevention of anemia